The Role of Entrepreneur Characteristic and Financial Literacy in Developing Business Success - Utomo, Mohamad Nur; Cahyaningrum, Widyastuti; Kaujan, Kaujan (Universitas Muhammadiyah Yogyakarta, 2020)
One important contribution of Small-and-Medium Enterprises (or SMEs) to the economic development is the absorption of workers. Absorbing more workers and reducing unemployment are achievable only if SMEs have been success in managing the sustainability of their business. The success of SMEs’ business is determined by few variables, which are to be examined in this research. Therefore, research is aimed to conduct empirical test over the effect of entrepreneur characteristic and financial literacy on business performance. Type of data is primary, which is acquired through distribution of questionnaire to respondents. Research sample includes Small-and-Medium Enterprises (SMEs) in Tarakan City. Analysis technique is Partial Least Square-Structural Equation Modelling (PLS-SEM). Result of research showed that personal characteristic, psychological characteristic, entrepreneur competency, and financial literacy are determinants to SMEs’ performance. Theoretical implication of this research is that research findings are supporting upper echelon theory and RBV theory when both theories explain factors that determine performance.